A method for stably obtaining embrittlement of ferrite-martensitic steel in an oxygen-saturated liquid lead-bismuth environment
By grinding, electrolytic polishing and ultrasonic cleaning on ferrite martensite steel specimens, and in-situ precorrosion treatment, the stability problem of ferrite martensite steel embrittlement in liquid lead-bismuth environment is solved, and the embrittlement effect in saturated liquid lead-bismuth environment is achieved, and the accuracy of scientific research is improved.
Patent Information
- Application Number
- CN202410568761.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-05-09
AI Technical Summary
In liquid lead-bismuth environments, ferrite martensite steel is prone to liquid metal embrittlement, resulting in degradation of material properties, and the prior art is difficult to achieve stable embrittlement effect in a saturated liquid lead-bismuth environment.
By grinding, electrolytic polishing and ultrasonic cleaning of the machined ferrite martensite steel specimens, and performing in-situ precorrosion treatment for 12 hours in the test machine, it is ensured that the specimens achieve good "wetting" and embrittlement in a saturated liquid lead-bismuth environment.
This method can stably obtain the embrittlement of ferrite martensite steel in a saturated liquid lead-bismuth environment, accurately simulate its mechanical response under actual working conditions in a liquid lead-bismuth environment, and improve the accuracy and significance of scientific research.
Smart Images

Figure CN118464558B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mechanical testing in a liquid lead-bismuth environment, and in particular to a method for stably obtaining embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment. Background Art
[0002] In recent years, the fourth-generation nuclear reactor has become the object of research and development in various countries due to its high reliability in safety and high efficiency in waste treatment. Lead-bismuth eutectic is expected to become the coolant of the fourth-generation reactor due to its excellent performance. Among them, ferritic martensitic steel is widely used as the metal of the reactor internal components due to its excellent performance. When it is in close contact with liquid lead-bismuth, that is, it has good "wettability" and is subjected to external force, it will cause the liquid metal embrittlement phenomenon of ferritic martensitic steel. The liquid metal embrittlement phenomenon will reduce the toughness and ultimate tensile strength of ferritic martensitic steel, and greatly reduce the low-cycle fatigue life, causing it to fail prematurely. The degradation of material properties caused by liquid metal embrittlement is one of the important issues restricting the practical application of the fourth-generation reactor. In recent years, the liquid metal embrittlement phenomenon of ferritic martensitic steel has been widely studied. However, under laboratory experimental conditions, ferritic martensitic steel in liquid lead-bismuth does not always undergo liquid metal embrittlement, which makes the study of liquid metal embrittlement difficult.
[0003] The external force on ferritic martensitic steel and its good "wettability" in the lead-bismuth environment are two important factors for the occurrence of liquid metal embrittlement. How to ensure good "wettability" between ferritic martensitic steel and liquid lead-bismuth when it is subjected to cyclic load becomes the key to the occurrence of liquid metal embrittlement. One of the important findings is that the oxide film generated on the surface of ferritic martensitic steel will reduce its "wettability" in the liquid lead-bismuth environment, and the formation of the oxide film is mainly through the ferritic martensitic steel being briefly exposed to the air or exposed to the saturated liquid lead-bismuth environment for a long time, and an oxide film that reduces "wettability" will be generated on its surface. In scientific experiments, a large part of the reason why ferritic martensitic steel does not achieve good "wettability" is that a protective oxide film grows on its surface, and part of the reason is that its surface has undergone mechanical polishing or electrolytic polishing, etc., which makes the surface of the specimen smooth and clean, which reduces its "wettability". In response to these findings, many operations have been carried out to improve the "wettability" of ferritic martensitic steel, most of which are aimed at eliminating the oxide film on its surface, including trying to clean the oxide film on the surface of ferritic martensitic specimens by ion beam sputtering, and then covering the surface of the specimen with lead-bismuth alloy as a coating by physical vapor deposition. When the ferritic martensitic steel specimens with lead-bismuth eutectic coatings were tested in liquid lead-bismuth under flowing helium, it was found that the "wettability" of ferritic martensitic steel would be improved. There was also an attempt to dissolve the oxide film on the surface of ferritic martensitic steel by chemical flux, and then weld lead-bismuth eutectic on its surface to improve its "wettability". It was subsequently found that the "wettability" of the surface of ferritic martensitic steel specimens would be improved, but the "wettability" inside was not high due to the lack of continuous adsorption of liquid lead-bismuth at the crack tip. Also, when ferrite martensitic steel is exposed to liquid lead bismuth under flowing hydrogen-helium mixture, the "wettability" of ferrite martensitic steel can be greatly improved in just a few hours by exposing it to low-oxygen liquid lead bismuth. When the temperature of liquid lead bismuth is increased from 150°C to 350°C, the "wettability" of ferrite martensitic steel exposed therein will also be improved. When the two are combined, the "wettability" of ferrite martensitic steel will increase to the highest level. However, roughening the surface of ferrite martensitic steel specimens may not necessarily improve their "wettability" and may even make the test inaccurate. Similarly, in a liquid lead environment, when ferrite martensitic steel is hardened and heat treated and a notch is opened on the surface of the specimen, its "wettability" in the liquid lead environment can also be increased, but the opening of the specimen will also increase the instability of the test results.
[0004] In summary, making the surface of the specimen rough, removing the surface oxide film with chemical flux and then welding lead-bismuth, etc. cannot stably obtain good "wettability", and although notching the specimen can improve the "wettability", it will make the test unstable. Methods such as cleaning the oxide film by ion beam sputtering and then depositing a lead-bismuth coating, exposing the specimen to a low-oxygen lead-bismuth environment, etc. will increase the requirements for experimental equipment and instruments, increase the cost of the test, and complicate the test. The present invention provides a method for stably obtaining the embrittlement of ferrite-martensitic steel in an oxygen-saturated liquid lead-bismuth environment, which can well avoid the above problems, provide a basic experimental method for conducting research on the influence of different factors on the embrittlement of liquid metals, and explore the mechanism of action of liquid metal embrittlement, and provide assistance for the construction and implementation of the fourth-generation reactor. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for stably obtaining the embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment, which can accurately simulate the mechanical response of ferrite martensitic steel under actual working conditions in a liquid lead-bismuth environment, stably obtain the embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment, and make scientific research accurate and meaningful.
[0006] The present invention solves the technical problem by the following technical solutions:
[0007] A method for stably achieving embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment comprises the following steps:
[0008] Step 1, grinding, electrolytic polishing and ultrasonic cleaning the machined ferrite martensitic steel specimen;
[0009] The machined ferrite martensitic steel specimens were polished with sandpapers of 1000 mesh, 2000 mesh, 3000 mesh and 5000 mesh, respectively, and then electrolytically polished. The ferrite martensitic steel specimens were immersed in alcohol for ultrasonic cleaning for 5 minutes. The ferrite martensitic steel specimens were taken out and the alcohol on the surface was dried with a hair dryer.
[0010] Step 2, clamping the ferrite martensitic steel specimen of step 1 on the testing machine, and servoing the load of the testing machine to zero during the clamping process;
[0011] Clear the load of the testing machine to zero, clamp the ferrite martensitic steel specimen in step 1 on the testing machine, start the load servo of the testing machine during the clamping process, and set the target to zero;
[0012] Step 3, placing solid lead and bismuth in the testing machine of step 2, turning on the heating to raise the temperature to a specified temperature, and subjecting the ferrite martensitic steel specimen to an in-situ pre-corrosion treatment for 12 hours in the testing machine;
[0013] Put solid lead-bismuth into the testing machine, turn on the heating to melt the lead-bismuth and continue to heat it to the specified temperature, keep it warm for 12 hours, keep the load servo of the testing machine open during the insulation process, set the target to zero, and set the test parameters through the testing machine;
[0014] Step 4: Test the ferrite martensitic steel specimen after in-situ pre-corrosion for 12 hours in step 3.
[0015] Furthermore, the electropolishing liquid used in the electrolytic polishing in step 1 is a mixed solution of alcohol and perchloric acid, and the volume ratio of alcohol to perchloric acid is 9:1.
[0016] The advantages and positive effects of the present invention are:
[0017] The method for stably obtaining the embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment of the present invention can accurately simulate the mechanical response of ferrite martensitic steel under actual working conditions in a liquid lead-bismuth environment, stably obtain the embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment, make scientific research accurate and meaningful, and has been supported by test results and microscopic analysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a flow chart of the method for stably obtaining embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment of the present invention;
[0019] Figure 2 (A) is a microscopic image of the fracture surface of a P91 steel specimen subjected to a low cycle fatigue test in an air environment in the inventor's experiment;
[0020] Figure 2 (B) is a microscopic image of the fracture surface of a P91 steel specimen in a low-cycle fatigue test in an oxygen-saturated liquid lead-bismuth environment without pretreatment in the inventor's experiment;
[0021] Figure 2 (C) is another fracture microscopic image of a P91 steel specimen in a low cycle fatigue test in an oxygen-saturated liquid lead-bismuth environment without pretreatment in the inventor's experiment;
[0022] Figure 2 (D) is a microscopic image of the fracture surface of a P91 steel specimen in an oxygen-saturated liquid lead-bismuth environment in a low-cycle fatigue test in situ pre-corrosion for 12 hours in the inventor's experiment;
[0023] Figure 3 (A) is a diagram of the crack source of the unpretreated fracture surface of a P91 steel specimen in a low-cycle fatigue test in an oxygen-saturated liquid lead-bismuth environment in the inventor's experiment;
[0024] Figure 3 (B) Figure 3 (A) EDS line scan analysis image shown;
[0025] Figure 3 (C) is a diagram of another fracture crack source of a P91 steel specimen in a low cycle fatigue test in an oxygen-saturated liquid lead-bismuth environment without pretreatment in the inventor's experiment;
[0026] Figure 3 (D) Figure 3 (C) EDS line scan analysis image shown;
[0027] Figure 3 (E) is a diagram of the crack source of the fracture of a P91 steel specimen in a low-cycle fatigue test in an oxygen-saturated liquid lead-bismuth environment after in-situ pre-corrosion for 12 hours;
[0028] Figure 3 (F) Figure 3 (E) EDS line scan analysis image shown. DETAILED DESCRIPTION
[0029] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0030] like Figure 1 As shown, a method for stably obtaining embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment comprises the following steps:
[0031] Step 1: Grind, electropolish and ultrasonically clean the machined ferrite martensitic steel specimens
[0032] The machined ferrite martensitic steel specimens were polished with sandpapers of 1000 mesh, 2000 mesh, 3000 mesh and 5000 mesh respectively, and the polishing standard was that when the polished ferrite martensitic steel specimens were observed under an optical microscope, only axial scratches along the symmetry axis of the specimens left by the polishing were found; then electrolytic polishing was performed, and the electropolishing liquid used in the electrolytic polishing was a mixed solution of alcohol and perchloric acid, and the volume ratio of alcohol to perchloric acid was 9:1; the ferrite martensitic steel specimens were immersed in alcohol for ultrasonic cleaning for 5 minutes, and the ferrite martensitic steel specimens were taken out and the surface alcohol was dried with a hair dryer;
[0033] Step 2, clamping the ferrite martensitic steel specimen of step 1 on the testing machine, and servoing the load of the testing machine to zero during the clamping process;
[0034] The load of the testing machine is reset to zero, and the ferrite martensitic steel specimen of step 1 is clamped on the testing machine. During the clamping process, the load servo of the testing machine is turned on, and the target is set to zero to ensure that no large stress is introduced into the ferrite martensitic steel specimen during the clamping process;
[0035] Step 3, placing solid lead and bismuth in the testing machine of step 2, turning on the heating to raise the temperature to a specified temperature, and subjecting the ferrite martensitic steel specimen to an in-situ pre-corrosion treatment for 12 hours in the testing machine;
[0036] Put solid lead-bismuth into the testing machine, turn on the heating to melt the lead-bismuth and continue to heat it to the specified temperature, keep it warm for 12 hours, keep the load servo of the testing machine open during the insulation process, set the target to zero, and set the test parameters through the testing machine;
[0037] Step 4: Test the ferrite martensitic steel specimen after in-situ pre-corrosion for 12 hours in step 3.
[0038] In the inventor's experiment, the P91 steel specimens were subjected to low cycle fatigue tests in an air environment at 350°C and an oxygen-saturated liquid lead-bismuth environment. The fatigue test adopted force control to ensure that the engineering stress was the same in each test. The results are shown in Table 1:
[0039] Test No. Test environment Preprocessing method Test life (cycles) Fracture characteristics Is there any lead or bismuth infiltration in the matrix? 1 Air —— 2595 toughness —— 2 Liquid Lead Bismuth No preprocessing 2720 toughness none 3 Liquid Lead Bismuth No preprocessing 2715 brittleness none 4 Liquid Lead Bismuth In-situ pre-corrosion for 12 hours 1269 brittleness have
[0040] Table 1
[0041] Test No. 1: Low cycle fatigue test of P91 steel specimen in air environment, test life is 2595 cycles;
[0042] Test No. 2: According to step 1 and step 2 of the method for stably obtaining embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment of the present invention, without pretreatment, solid lead-bismuth is placed in the testing machine, and the temperature is raised to a specified temperature and then kept warm for 30 minutes. The P91 steel specimen is turned on and subjected to a low-cycle fatigue test in an oxygen-saturated liquid lead-bismuth environment, and the test life is 2720 cycles;
[0043] Test No. 3: According to step 1 and step 2 of the method for stably obtaining embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment of the present invention, without pretreatment, solid lead-bismuth is placed in the testing machine, and the temperature is raised to the specified temperature and kept warm for 30 minutes before the P91 steel specimen is turned on for low-cycle fatigue test in an oxygen-saturated liquid lead-bismuth environment, and the test life is 2715 cycles;
[0044] Test No. 4: Through the steps 1, 2, 3 and 4 of the method for stably obtaining embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment of the present invention, the in-situ pre-corrosion was started for 12 hours and the P91 steel specimen was subjected to a low-cycle fatigue test in an oxygen-saturated liquid lead-bismuth environment, and the test life was 1269 cycles;
[0045] like Figure 2 As shown in (A), the fracture surface of the P91 steel specimen in the air environment of test number 1 is tough as a whole, and there are multiple crack initiation points; Figure 2As shown in (B), the fracture surface of the unpretreated P91 steel specimen in the oxygen-saturated lead-bismuth environment of test number 2 is tough overall, and there are multiple crack initiation points similar to those in the air environment, such as Figure 2 As shown in (C), the fracture of the untreated P91 steel specimen in the oxygen-saturated lead-bismuth environment of test number 3 is brittle overall, with only one crack initiation point. Regardless of whether the fracture characteristics of the untreated test are brittle, the life of the untreated test is not much different from that of the comparison test in the air environment, which proves that the untreated test does not accurately simulate the mechanical response of P91 steel in the liquid lead-bismuth environment under actual working conditions. Figure 2 As shown in (D), the fracture of the P91 steel specimen of test number 4 in a saturated lead-bismuth environment after in-situ pre-corrosion for 12 hours on a testing machine is brittle overall, with only one crack initiation point, and its life is significantly reduced compared to that in an air environment. It can be seen that the mechanical test in a saturated lead-bismuth environment after a 12-hour in-situ pre-corrosion pretreatment can accurately simulate the mechanical response of ferrite martensitic steel under actual working conditions in a liquid lead-bismuth environment, stably obtain the embrittlement of ferrite martensitic steel in a saturated liquid lead-bismuth environment, and make scientific research accurate.
[0046] like Figure 3 As shown in (A), (B), (C), and (D), for test number 2 and test number 3, there is no penetration of lead and bismuth elements into the matrix near the crack source of the unpretreated fracture of the P91 steel specimen in the low-cycle fatigue test in the oxygen-saturated liquid lead-bismuth environment; Figure 3 As shown in (E) and (F), the P91 steel specimen was pre-corroded in situ for 12 hours in a low-cycle fatigue test in an oxygen-saturated liquid lead-bismuth environment. There was obvious lead and bismuth element penetration in the matrix near the fracture crack source. It can be seen that the penetration of lead and bismuth elements is a necessary condition for the fatigue embrittlement of P91 steel in liquid lead-bismuth. Scientific research has found that "wettability" and external force are two conditions for the occurrence of liquid metal embrittlement. "Wettability" requires that lead and bismuth atoms have penetrated into the matrix at the crack tip before liquid metal embrittlement occurs, rather than when the crack is generated, the lead and bismuth atoms will quickly adsorb to the crack tip to produce "wetting". Therefore, since the unpretreated specimen was not pre-corroded for a suitable time, there was no penetration of lead and bismuth atoms in the matrix, and the "wettability", one of the two conditions for liquid metal embrittlement, was not achieved. Liquid metal embrittlement did not occur, and the experiment under this condition lost the significance of scientific research.
[0047] In summary, the in-situ pre-corrosion of ferritic martensitic steel for 12 hours before the mechanical test in the liquid lead-bismuth environment is a necessary condition for the occurrence of liquid metal embrittlement. Only with a long period of pre-corrosion can the mechanical response of ferritic martensitic steel under actual working conditions be accurately simulated, and the embrittlement of ferritic martensitic steel can be stably obtained in the saturated liquid lead-bismuth environment, making scientific research accurate and meaningful.
[0048] Although the embodiments and drawings of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.
Claims
1. A method for stably embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment, characterized in that: The following steps are included: Step 1, grinding, electrolytic polishing and ultrasonic cleaning the machined ferrite martensitic steel specimen; The machined ferrite martensitic steel specimens were polished with sandpapers of 1000 mesh, 2000 mesh, 3000 mesh and 5000 mesh, respectively, and then electrolytically polished. The ferrite martensitic steel specimens were immersed in alcohol for ultrasonic cleaning for 5 minutes. The ferrite martensitic steel specimens were taken out and the alcohol on the surface was dried with a hair dryer. Step 2, clamping the ferrite martensitic steel specimen of step 1 on the testing machine, and servoing the load of the testing machine to zero during the clamping process; Clear the load of the testing machine to zero, clamp the ferrite martensitic steel specimen in step 1 on the testing machine, start the load servo of the testing machine during the clamping process, and set the target to zero; Step 3, placing solid lead and bismuth in the testing machine of step 2, turning on the heating to raise the temperature to a specified temperature, and subjecting the ferrite martensitic steel specimen to an in-situ pre-corrosion treatment for 12 hours in the testing machine; Put solid lead-bismuth into the testing machine, turn on the heating to melt the lead-bismuth and continue to heat it to the specified temperature, keep it warm for 12 hours, keep the load servo of the testing machine open during the insulation process, set the target to zero, and set the test parameters through the testing machine; Step 4: Test the ferrite martensitic steel specimen after in-situ pre-corrosion for 12 hours in step 3.
2. The method for stably embrittlement of ferrite martensitic steel in an oxygen-saturated liquid lead-bismuth environment according to claim 1, characterized in that: The electropolishing liquid used in the electrolytic polishing in step 1 is a mixed solution of alcohol and perchloric acid, and the volume ratio of alcohol to perchloric acid is 9:1.
Citation Information
Patent Citations
Device and method for testing material embrittlement under liquid metal condition
CN102620990A
Dynamic mechanical property testing device in high-temperature lead-bismuth environment
CN117470693A